2020
DOI: 10.1002/smll.201906861
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Therapeutic Nanoparticle That Alters Tau Protein and Ameliorates Tauopathy Toward a Functional Nanomedicine to Tackle Alzheimer's

Abstract: Tauopathy is a complex disorder associated at the junction of several other pathologies. Intrinsically disordered tau protein remains therapeutically challenging due to its undruggable nature and is a possible reason for monumental failure of several tau‐based therapies. Herein, nanogold remodeled tau is reported as a pseudo‐nanochaperon and shows therapeutic benefit by passive targeting in transgenic tau P301L mutant mice. Treatment with nanogold polyethylene glycol (Au‐PEG) conjugate moderately improves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…535 Vimal and colleagues also reported the ability of pegylated AuNPs (B30 nm) to reduce the symptomatology in a t-P301L transgenic mouse model by inhibiting t oligomerization. 536 Recently, Shiu and collaborators developed a novel electrochemical assay to detect t-381 (an early marker of AD). An anti-t Ab and an aptamer were used to recognize the t-381 molecule, while cysteamine-stabilized AuNPs promoted the signal amplification.…”
Section: Pre-clinical Gold-based Strategies For Neurological Disordersmentioning
confidence: 99%
“…535 Vimal and colleagues also reported the ability of pegylated AuNPs (B30 nm) to reduce the symptomatology in a t-P301L transgenic mouse model by inhibiting t oligomerization. 536 Recently, Shiu and collaborators developed a novel electrochemical assay to detect t-381 (an early marker of AD). An anti-t Ab and an aptamer were used to recognize the t-381 molecule, while cysteamine-stabilized AuNPs promoted the signal amplification.…”
Section: Pre-clinical Gold-based Strategies For Neurological Disordersmentioning
confidence: 99%
“…S8, ESI †). 32 In our previous in vitro study, we found that the exogenous addition of pathological A4V SOD1 impairs motor movement of the MT cytoskeleton. 10 However, the addition of Au NPs repairs the A4SOD1-affected MT and restore MT kinesin processivity.…”
Section: Resultsmentioning
confidence: 85%
“…We have synthesized a gold nanoconjugate (Au-PEG) according to the reported literature. 32 We also used Au NPs from a commercial source. The compound was characterized using TEM and Zetasizer apparatus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations